Արաբական փոխառությունները Ստ. Մալխասյանցի «Հայերեն բացատրական բառարան»-ում - Միքայելյան, Ս․ Ա․
В статье рассматриваются арабские заимствования армянского языка согласно ‘‘Армянского толкового словаря’’ Ст. Малхасянца. Исследование показывает, что часть слов продуктивна и сегодня, некоторые слова используются параллельно с армянскими эквивалентами, а некоторая часть вытеснялась из активного запаса слов. The article studies the Arabic borrowings of Armenian according to Armenian explanatory dictionary compiled by St. Malkhasyants. Research shows that a group of words are still viable in Armenian today, a group of words are used in parallel with the Armenian equivalent, and a number of words, having lost their viability, have been pushed out of the active vocabulary
Keywords: Լեզվաբանություն